Egg yolk cholesterol, egg quality, and performance in response to copper–methionine chelates and alfalfa powder supplementation in Nick chick laying hen diets - A. S. Noori; Z. Jameel; A. A. Saki; P. Zamani; S. Mirzaei Goudarzi (Journal of the Indonesian Tropical Animal Agriculture, 2023)
This experiment was designed to investigate the effects of different levels of copper–methionine chelates and alfalfa powder on egg yolk cholesterol content, egg quality, and performance in laying hens. In this experiment, a total of 100 laying hens (Nick Chick strain, from 109 to 117 weeks of age) were arranged into five experimental treatments, consisting of 2 different dietary alfalfa powder and 2 different copper chelate levels in a (2x2) factorial completely randomized design (CRD). The treat-ments groups included: T1 Control (Corn and soybean meal), treatments T2 (3% alfalfa powder+50 mg/kg copper-methionine chelate), T3 (3% alfalfa powder+100 mg/kg copper-methionine chelate), T4 (6% alfalfa powder+50 mg/kg copper-methionine chelate) and T5 (6% alfalfa powder+100 mg/kg cop-per-methionine chelate). The results of this study have shown that, different levels of alfalfa powder and copper-methionine chelate in laying hens diet except feed conversion ratio and shell-less eggs, oth-er performance parameters were not substantially affected by the level of 3% alfalfa powder through-out of experimental period (P>0.05). Moreover, different levels of alfalfa powder and copper-methionine chelate except egg yolk color had no significant effect on internal and external egg quality traits during the whole experimental period (P>0.05). As well as, the egg yolk color index was signifi-cantly increased by increasing the level of alfalfa powder in the laying hens’ diet (P<0.001). The high-est egg yolk color index was observed in treatment 5 which (containing 6% alfalfa powder+ 100 mg / kg copper-methionine chelate in per kg of diet). Meanwhile, the treatment group that received (6% al-falfa powder+100mg/kg copper- methionine chelate) the egg yolk cholesterol concentration was signif-icantly decreased compared to the control group (P<0.001). Therefore, addition of alfalfa powder and copper methionine chelate to the diet of laying hens reduced egg yolk cholesterol and increased egg yolk color.